1996
DOI: 10.1037/0096-1523.22.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual repetition blindness effects.

Abstract: Repetition blindness (RB) may reveal a new limitation on human perceptual processing. Recently, however, researchers have attributed RB to postperceptual processes. The standard rapid serial visual presentation (RSVP) paradigm used in most RB studies is open to such objections. The "single-frame" paradigm introduced by J. C. Johnston and B. L. Hale (1984) allowed investigation of RB with minimal memory demands. Participants made a judgment about whether 1 masked target word was the same or different than a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
75
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 21 publications
9
75
2
Order By: Relevance
“…In addition, it has been demonstrated that repetition blindness occurs when memory demands are reduced (Chun, 1997;Dux & Marois, 2007;Luo & Caramazza, 1995 and even when no recall is required (Hochhaus & Johnston, 1996;Johnston et al, 2002). Thus, although retrieval failure contributes to some effects of repetition seen in RSVP streams, it is not responsible for all of them.…”
Section: Implications For Theories Of Repetition Blindnessmentioning
confidence: 99%
“…In addition, it has been demonstrated that repetition blindness occurs when memory demands are reduced (Chun, 1997;Dux & Marois, 2007;Luo & Caramazza, 1995 and even when no recall is required (Hochhaus & Johnston, 1996;Johnston et al, 2002). Thus, although retrieval failure contributes to some effects of repetition seen in RSVP streams, it is not responsible for all of them.…”
Section: Implications For Theories Of Repetition Blindnessmentioning
confidence: 99%
“…When the primes are presented for a relatively long interval, and subjects are encouraged to attend to them, subjects tend to prefer the foil probe if the target is repetition primed. Thus, target identification accuracy is reduced under repetition priming, an impairment that parallels repetition blindness in RSVP lists (see also Hochhaus & Johnston, 1996). In the ROUSE model, one accounts for that deficit by assuming that subjects discount evidence that potentially has been generated by an irrelevant source (i.e., evidence that could have arisen from the prime event is discounted).…”
Section: Repetition Blindness As Perception or Memory?mentioning
confidence: 99%
“…Thus, tokenization of the second presentation of a repeated word fails, and it cannot be reported. In the type-token account of repetition blindness, then, the impaired report of a repeated item is attributed to a failure of encoding or perception that occurs at the moment a repeated word is presented in an RSVP list (see also Hochhaus & Johnston, 1996;Johnston, Hochhaus, & Ruthruff, 2002). …”
mentioning
confidence: 99%
“…According to either of these 'accounts, Park and Kanwisher's d' measure of RB would constitute not a failure to perceive repeated items, but rather a failure to remember or correctly categorize them. Hochhaus and Johnston (1996) report a series of experiments designed to get around these difficulties. They used the "single-frame" paradigm (Johnston & Hale, 1984) to measure RB, in which memory load is low because participants make only a single judgment: whether a masked target word is the same as or different from a posttarget probe word.…”
mentioning
confidence: 99%
“…detection of single words presented near threshold (Hochhaus & Johnston, 1996;Humphreys, Besner, & Quinlan, 1988;Marohn & Hochhaus, 1988), misspelling detection (MacKay, 1969), and judgments of the number of letters that appear in a simultaneous spatial array (Mozer, 1989). Kanwisher (1987Kanwisher ( , 1991 argued that repetition blindness is primarily of interest because it reveals an important functional dissociation between two different visual processes.…”
mentioning
confidence: 99%